Comparative Analysis of Divination (Ifá) in Yorubaland and Russian Societies - Adeoti, Yakubu Adegboyega; Olaleye, Samuel Kayode (NIU Journal of Humanities, 2026)
Human’s existence is prone to different forms of challenges, which could be physical, emotional or spiritual. Human beings have always looked for answers to the mysteries they encounter in their lives. There is archeological evidence that a need to know and deep spiritual seeking are universal human traits, and that some form of divination has been used since the earliest times, to support this quest. Divination is a way of exploring the unknown in order to elicit answers (that is, oracles) to questions beyond the range of ordinary human understanding. All known peoples on earth have practiced some form of divination. Divination can be done with things, such as consecrated or significant objects, bones, shells, stones, tea leaves, or cards. This paper adopts symbolic and interpretative approaches for its analysis. Ifá religion is orally transmitted from one generation to another rather than scriptural. The religion believes in a Supreme Being, divinities, spirits, veneration of ancestors , and mysterious powers that have to do with magic, and  traditional medicine . The religion can be found through art, rituals and festivals, beliefs and customs, names of people and places, songs and dance, proverbs, and myths. Many studies of East Slavic paganism are based on written sources. These are scant and consist mainly of brief chronicle entries, sermons, and instructions, dating from the Christian era. East Slavic written sources give a list of probable deities, and, occasionally, their attributes and functions.  Keywords: Divination, Ifa, Paganism, Spirits, Deities.